Bibliometric Analysis of a Decade Orchidaceae Research: A Comprehensive Study in the Agriculture Field - Tina, Siti Agus; Armini, Ni Made; Krisantini (Department of Agronomy and Horticulture, IPB University, 2024)
Orchidaceae is a family of flowering plants esteemed in numerous countries globally, so they are a promising subject for further exploration. The evolution of Orchidaceae research over the past decade is a foundation for identifying areas warranting deeper investigation. bibliographic analysis based on the Scopus database was used to elucidate the advancements in research over a decade. We brought data on an increasing number of publications between 1943 to 2023. About 7139 documents were found about orchid research, and 59% were in agriculture filtered by subject area, from around 2013 until 2023. America and Asia have the most significant number of Orchidaceae species, approximately 12000. However, China stands out with many publications with a high citation rate. Regarding the organization that publishes the journal, from 16204 organizations, the University of Chinese Academy is a prominent contributor characterized by substantial collaboration in advancing orchid research. Furthermore, the co-occurrence and all keywords indicating genetics, biodiversity, and taxonomy have been used as basis research topics in the last ten years. With additional analyses and reviews, this bibliometric analysis demonstrates that the research on Orchidaceae, specifically in agriculture, thrives every decade. Hence, we recommend future orchid conservation and research that should focus on the current gaps in knowledge and practice, including species distributions, management of species, and threats of extinction for developing or creating new cultivars to intensify a high potential commercial value.